ACUTE INTAKE OF A LARGE DOSE OF CARDIAC GLYCOSIDES BY A YOUNG MALE - L. Savchenko; I. Mormol; P. Husar; N. Reva; O. Borzykh; I. Kaydashev (Проблеми екології та медицини)
One of the most toxic drugs is a group of cardiac glycosides. Having a very narrow spectrum of therapeutic action, cardiac glycosides are able to cause serious intoxication with complications including arrhythmias and conduction disorder, which often lead to death. Considering the mortality rates in cases of medication poisoning, it is important to pay special attention and care to prevent, diagnose and treat such medical conditions. The 28-year-old male presents with intoxication and arrhythmia after he unintentionally took a wrong medication. A timely appeal for medical help and appropriate treatment helped to avoid serious consequences of glycoside intoxication.